EFEKTIFITAS PENGGUNAAN SURAT PERNYATAAN TANGGUNG JAWAB MUTLAK (SPTJM) DALAM RANGKA PERCEPATAN PENINGKATAN CAKUPAN KEPEMILIKAN AKTA KELAHIRAN DI SUKU DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA ADMINISTRASI JAKARTA BARAT (Lex Jurnalica, 2023)
AbstractThe issuance of the Minister of Home Affairs Regulation Number 9 of 2016 concerning the Acceleration of Increasing the Coverage of Birth Certificate Ownership as revoked based on the Minister of Home Affairs Regulation Number 108 of 2019 concerning Implementing Regulations of Presidential Regulation Number 96 of 2018 concerning Requirements and Procedures for Population Registration and Civil Registration and Ministerial Regulations Domestic Affairs Number 109 of 2019 concerning Forms and Books Used in Population Administration allows for a Statement of Absolute Responsibility (SPTJM) to be made as a substitute for supporting documents that do not exist or are not found in the making of a birth certificate. This innovation was carried out to make it easier for residents to get public services in the field of population administration, especially in the management of birth certificates. Juridically, this allows the issuance of birth certificates which contain the phrase